Chronic immunoglobulin maintenance therapy in myasthenia gravis. (15th October 2020) - Alcantara, M.; Sarpong, E.; Barnett, C.; Katzberg, H.; Bril, V.
Abstract : Background and purpose: Long‐term treatment of myasthenia gravis (MG) includes symptomatic and course‐modifying therapies that target the immune system. Recently, both intravenous immunoglobulin (IVIG) and subcutaneous immunoglobulin (SCIG) have emerged as viable options for chronic therapy, considering the favourable safety–efficacy profile and possible immunosuppressant sparing properties. The aim was to investigate the outcomes of the long‐term care of generalized MG with immunoglobulin (Ig). Methods: This is a retrospective, repeated‐measures design study. Charts of generalized MG patients, treated with IVIG/SCIG for at least 6 months, from January 2015 to January 2020, were analysed. The primary outcome was the mean change in Myasthenia Gravis Impairment Index (MGII) after treatment with Ig, comparing baseline to IVIG and SCIG treatment periods. Secondary outcomes included the changes in pyridostigmine, immunosuppressive medications and patient‐reported outcome 'percentage of normal' (0%–100%). Results: Thirty‐four patients were treated with chronic Ig therapy (30 IVIG/SCIG, three SCIG, one IVIG). The mean durations of IVIG and SCIG periods were 21.8 ± 19.4 (range 3–64) months and 19.5 ± 11.3 (range 5–45) months respectively. There was a significant reduction in MGII scores (27.7 ± 15.7 baseline; 22.0 ± 17.4 IVIG period; 19.5 ± 18.1 SCIG period; F = 17.9; d.f. = 1.7; P < 0.01), pyridostigmine and immunosuppressant use ( P = 0.00). The outcome 'percentage of normal' had a significant positive association with both treatments ( P = 0.00). Conclusion: Our study results suggest that patients can be successfully transitioned to IVIG and from IVIG to SCIG in the chronic treatment of generalized MG with reductions in impairments and use of other medications and improvement in overall status with Ig therapy. Prospective, randomized studies are needed to clarify costs and comparative effectiveness. Abstract : This retrospective study of 34 patients with generalized MG showed a successful transition from IVIG to SCIG therapy. Chronic IVIG for about 20 months, followed by transition to SCIG therapy for another 20 months was associated with improved MG status and reduced immunosuppressive therapy requirements.